A taxonomic review of the Neotropical genus Hansreia Halffter & Martínez, 1977 (Coleoptera: Scarabaeidae, Scarabaeinae) - Valois, Marcely; Vaz-De-Mello, Fernando Z.; Silva, Fernando A. B. (Zootaxa, 2015)
The taxonomy of the genus Hansreia Halffter & Martínez is reviewed. The genus consists of six species, including three new species: H. peugeoti sp. nov., H. grossii sp. nov., H. krinskii sp. nov. Lectotypes are designated for Hansreia affinis (Fabricius 1801), H. oxygona (Perty 1830) [here considered a valid species] and H. coriacea (Schmidt 1922). The species status of H. coriacea is recognized. A detailed literature review, synonymies, description, illustration of key morphological characters as well as data of the studied material and geographic distribution is provided for each species.